Persistent Response and Prolonged Survival Following Pembrolizumab Discontinuation Due to Long-Lasting Autoimmune Colitis in Advanced NSCLC: A Case Report - Damato, Angela; De Marco, Loredana; Serra, Silvia; Larocca, Mario; Arias, Alicia Garcia; Rondini, Ermanno; Pinto, Carmine (Frontiers in Oncology, 2021)
Pembrolizumab is a programmed death receptor-1 (PD-1) inhibitor that has been approved for treatment of a wide variety of malignancies including non-small-cell lung cancer (NSCLC). Immune-mediated colitis is a known adverse effect of pembrolizumab which can lead to the treatment interruption, although not compromising the control of the oncological disease. Herein, we report the case of a 59-year-old woman on pembrolizumab for advanced NSCLC which developed a severe and persistent colitis treated with infliximab for several months following anti-PD-1 antibody discontinuation. This strategy resulted in an improvement but not complete recovery of the gastrointestinal toxicity despite revealed sustained response and control of the oncological disease with prolonged survival over 24 months.